An automatic hybrid method for retinal blood vessel extraction - Yang, Yong; Huang, Shuying; Rao, Nini (Zielona Góra: Uniwersytet Zielonogórski)
The extraction of blood vessels from retinal images is an important and challenging task in medical analysis and diagnosis. This paper presents a novel hybrid automatic approach for the extraction of retinal image vessels. The method consists in the application of mathematical morphology and a fuzzy clustering algorithm followed by a purification procedure. In mathematical morphology, the retinal image is smoothed and strengthened so that the blood vessels are enhanced and the background information is suppressed.
Keywords: blood vessel extraction; retinal image; mathematical morphology; fuzzy clustering